Farmers’ perception of termites in agriculture production and their indigenous utilization in Northwest Benin - Yêyinou Loko, Laura Estelle (J Ethnobiol Ethnomed, 2017)
BACKGROUND: Although termites are considered as agricultural pests, they play an important role in maintaining the ecosystem. Therefore, it matters to investigate the farmers’ perception of the impacts of the termites on the agriculture and their indigenous utilization. METHODS: A semi-structured questionnaire was used to interview 94 farmers through 10 villages of Atacora department, in the northwestern region of Benin, to obtain information for the development of successful strategies of termite management and conservation. Their perceptions on the importance and management of termites along with the indigenous nomenclature and utilization of termite mounds were assessed. Termite species identified by farmers were collected and preserved in 80% alcohol for identification. RESULTS: Eight crops were identified by farmers as susceptible to termites with maize, sorghum, and yam as being the most susceptible. According to farmers, the susceptibility to termites of these crops is due to their high-water content and sweet taste. A total of 27 vernacular names of termites were recorded corresponding to 10 species, Amitermes evuncifer, Macrotermes subhyalinus, and Trinervitermes oeconomus being the most damaging termite species. All the names given to termite species had a meaning. The drought was identified by farmers as the main factor favouring termite attacks. Demolition of termite mounds in the fields was the most commonly reported control method. Salt and other pesticides were commonly used by farmers to protect stored farm products. The lack of effective control methods is the main constraint for termite management. In northwestern Benin, farmers reported different purpose utilizations of termite mounds and termites. CONCLUSIONS: The study has shown that farmers perceived termites as pests of several agricultural crops and apply various indigenous control practices whose efficiency need to be verified. Utilization of termites and termite mound soil as food and medicinal resources underlines the need for a more focused approach to termite control for the conservation of non-pest termite species. The sensitization of farmers on the importance of termites as well as the development of an integrated control method to combat termite pests proved necessary.